I know this is not the place to ask math questions, but since Im doing an online math class, Its hard for me to ask a real person.
In my Math textbook, Im having a hard time understanding this problem, I know its something simple, I just cant figure out what. The fact that Im dum at math isnt helping any.
Simplify: -2(x-5)+ 4(2x + 2)
This is how the book says to simplify.
-2(x-5)+ 4(2x + 2) = -2*x + (-2)(-5) + 4*2x + 4/2
= -2x + 10 + 8x +8
= 6x + 18
This is how it seems to me it should go, which gives it a totaly different answer.
-2(x-5)+ 4(2x + 2) = -2*x -(-2)(-5) + 4*2x + 4/2
= -2x - 10 + 8x +8
= -2x + (-10) + 8x +8
= 6x + (-2) or = 6x - 2
So what am I doing wrong? Why are they changing the minus sign to a plus sign when they are caculating, for no reason at all?
* = mutiply